2019
DOI: 10.2147/ijn.s205350
|View full text |Cite
|
Sign up to set email alerts
|

<p>Alginate nanoparticles as non-toxic delivery system for miltefosine in the treatment of candidiasis and cryptococcosis</p>

Abstract: Introduction and objective Previous studies indicate that miltefosine (MFS) may be an alternative as an antifungal agent; however, it presents several adverse effects. Thus, the aim of this study was to produce miltefosine-loaded alginate nanoparticles (MFS.Alg) for toxicity reduction to be used as an alternative for the treatment of cryptococcosis and candidiasis. Methods Alginate nanoparticles were produced using the external emulsification/gelation method, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 63 publications
9
38
0
7
Order By: Relevance
“…Miltefosine has also been used successfully in a limited number of cases of the extremely rare highly lethal brain infection by the amoeba Naegleria fowleri and, in the United States, has orphan drug status for the treatment of other amebic infections [62]. Our group and others have previously described the antifungal activity of miltefosine [63][64][65][66][67][68]. Iodoquinol (also referred to as diiodohydroxyquinoline) is an halogenated quinoline derivative (see Supplementary Figure S1) that is used as an intestinal antiparasitic drug, mainly in the treatment of Entamoeba histolytica infections [69], apparently acting by chelation of ferrous ions essential for metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Miltefosine has also been used successfully in a limited number of cases of the extremely rare highly lethal brain infection by the amoeba Naegleria fowleri and, in the United States, has orphan drug status for the treatment of other amebic infections [62]. Our group and others have previously described the antifungal activity of miltefosine [63][64][65][66][67][68]. Iodoquinol (also referred to as diiodohydroxyquinoline) is an halogenated quinoline derivative (see Supplementary Figure S1) that is used as an intestinal antiparasitic drug, mainly in the treatment of Entamoeba histolytica infections [69], apparently acting by chelation of ferrous ions essential for metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…, Cryptococcus spp. [32,33,[45][46][47][48][49][50][51], Aspergillus spp. [13,29,35,[52][53][54][55][56][57][58][59][60][61], Mucorales [62][63][64], Madurella mycetomatis [65][66][67], and other fungal agents [68][69][70].…”
Section: Evaluation Of Antifungal Efficacy In Galleria Mellonellamentioning
confidence: 99%
“…The genus Candida has been extensively studied in the G. mellonella model especially for the evaluation of virulence and antifungal efficacy [10,71,72]. G. mellonella was used to test the efficacy of different antifungal compounds against Candida yeasts including conventional antifungal drugs [13][14][15][16][17][18][19][20][21][22][23], new drugs [25][26][27][30][31][32]34] or non-antifungal compounds in a repurposing perspective [24,28,29,33]. Antifungal combinations against Candida spp.…”
Section: Candida Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that MFS has a broad-spectrum in vitro antifungal activity, including against C. gattii and C. neoformans isolates in the both planktonic (0.25-4 µg/mL) and biofilm (8 -≥16 µg/mL) lifestyles [79][80][81]. Moreover, MFS was effective to control the fungal infection in the larval model of Galleria mellonella by C. gattii at 10, 20, and 40 mg/kg [82]. MFS at 3.6 and 7.2 mg/kg/day has shown effectiveness in the murine model of disseminated cryptococcosis [80] although this result has been conflicting with other work [83].…”
Section: Miltefosine (Mfs)mentioning
confidence: 99%